2016
DOI: 10.1371/journal.pone.0151738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trifecta and Pentafecta Outcomes between T1a and T1b Renal Masses following Robot-Assisted Partial Nephrectomy (RAPN) with Minimum One Year Follow Up: Can RAPN for T1b Renal Masses Be Feasible?

Abstract: Purpose/ObjectivesTo investigate the feasibility of RAPN on T1b renal mass by assessment of Trifecta and Pentafecta rate between T1a and T1b renal mass.Materials/MethodsWe retrospectively reviewed the medical records of 277 cases of RPN performed from 2006 to 2015. Sixty patients with clinically T1b renal masses (> 4cm and ≤ 7 cm) were identified, and from 180 patients with clinically T1a renal mass, 60 patients were matched with T1b renal mass by propensity score. Tumor complexity was investigated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 22 publications
(32 reference statements)
5
48
1
1
Order By: Relevance
“…The principal factor driving this seemingly ‘low’ rate of optimum outcome achievement is our renal function outcome, which is more stringent than other composite outcomes because it is based on GFR preservation and CKD upstaging instead of ischaemia time alone; however, when critically compared, our results are similar to those found in the literature. For example, in an analysis of RAPN outcomes for T1a and T1b renal masses of similar size and complexity to those included in the present study, Kim et al reported trifecta achievement rates of 65% and 43% for T1a and T1b masses, respectively, which are similar to our reported RAPN rates of 66% and 40%. In a multicentre study of RAPN for small renal masses, Zargar et al reported trifecta and pentafecta rates of 70% and 39%, respectively, which are slighlty better than our RAPN rates for T1a masses (66% and 28%); however, the larger size of masses in the present cohort may account for this difference .…”
Section: Discussionsupporting
confidence: 88%
“…The principal factor driving this seemingly ‘low’ rate of optimum outcome achievement is our renal function outcome, which is more stringent than other composite outcomes because it is based on GFR preservation and CKD upstaging instead of ischaemia time alone; however, when critically compared, our results are similar to those found in the literature. For example, in an analysis of RAPN outcomes for T1a and T1b renal masses of similar size and complexity to those included in the present study, Kim et al reported trifecta achievement rates of 65% and 43% for T1a and T1b masses, respectively, which are similar to our reported RAPN rates of 66% and 40%. In a multicentre study of RAPN for small renal masses, Zargar et al reported trifecta and pentafecta rates of 70% and 39%, respectively, which are slighlty better than our RAPN rates for T1a masses (66% and 28%); however, the larger size of masses in the present cohort may account for this difference .…”
Section: Discussionsupporting
confidence: 88%
“…Kim et al 7 and Porpiglia et al 8 reported Trifecta outcomes in 43and 69.5% of robot-assisted surgical T1b patients, respectively. In both of these studies WIT ≤ 25 minutes was used for evaluation of renal function preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and colleagues retrospectively analyzed 277 patients of renal cell carcinoma undergoing RPN and reported 38.3% of Pentafecta achievement for T1a patients and 26.7% for T1b patients. 19 Our study also analyzed patients with ‡4 cm renal tumors. Rates of Pentafecta achievement for patients with ‡4 cm renal tumors decreased to 25.0% in patients receiving TRPN and 16.1% for patients receiving RRPN.…”
Section: Discussionmentioning
confidence: 99%